2007
DOI: 10.1111/j.1471-4159.2007.05125.x
|View full text |Cite
|
Sign up to set email alerts
|

Myosin IIA is required for neurite outgrowth inhibition produced by repulsive guidance molecule

Abstract: Although myelin‐associated neurite outgrowth inhibitors express their effects through RhoA/Rho‐kinase, the downstream targets of Rho‐kinase remain unknown. We examined the involvement of myosin II, which is one of the downstream targets of Rho‐kinase, by using blebbistatin – a specific myosin II inhibitor – and small interfering RNA targeting two myosin II isoforms, namely, MIIA and MIIB. We found that neurite outgrowth inhibition by repulsive guidance molecule (RGMa) was mediated via myosin II, particularly M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 36 publications
3
50
0
Order By: Relevance
“…The RGMA protein acts through the activation of a RhoA/Rho kinase-dependent pathway activation of myosin II. [42][43][44] Inhibition of Rho family functions has been shown to ameliorate EAE in rats, associated with promotion of myelin repair, inhibition of leukocyte infiltration into the central nervous system and a reduced axonal damage. [45][46][47] The strong expression of RhoA in active MS lesions and low expression in chronic MS lesions suggest that RhoA also has a role in MS. 47 We can thus hypothesize that variants of RGMA through differential regulation of RhoA result in different immune activation and disease outcome.…”
Section: Eae30mentioning
confidence: 99%
“…The RGMA protein acts through the activation of a RhoA/Rho kinase-dependent pathway activation of myosin II. [42][43][44] Inhibition of Rho family functions has been shown to ameliorate EAE in rats, associated with promotion of myelin repair, inhibition of leukocyte infiltration into the central nervous system and a reduced axonal damage. [45][46][47] The strong expression of RhoA in active MS lesions and low expression in chronic MS lesions suggest that RhoA also has a role in MS. 47 We can thus hypothesize that variants of RGMA through differential regulation of RhoA result in different immune activation and disease outcome.…”
Section: Eae30mentioning
confidence: 99%
“…Although NMII isoforms share somewhat overlapping roles, each isoform has distinctive tissue distribution and specific functions. NMII-A is important for neural growth cone retraction (17,18) and is distributed to the front of migrating endothelial cells (19). While NMII-B participates in growth cone advancement (20) and was detected in the retracting tails of migrating endothelial cells (19).…”
Section: Non Muscle Myosin II (Nmii)mentioning
confidence: 99%
“…Recently, it was reported that RGMa regulated cephalic neural tube closure in mouse embryo and neuronal apoptosis (Niederkofler V et al, 2004;Matsunaga E et al, 2004;. In the pathological context, we demonstrated that RGMa inhibited neurite outgrowth and hindered functional recovery after spinal cord injury (Hata et al, 2006;Kubo T et al, 2008). While the functions of RGMa in the CNS have been wellestablished, its functions in other organs have remained uncertain.…”
Section: Repulsive Guidance Molecule a (Rgma) That Has Pivotal Roles mentioning
confidence: 85%
“…During our effort to identify a new member of axon outgrowth inhibitors, we discovered that the repulsive guidance molecule a (RGMa), which is expressed in neurons and oligodendrocytes in the CNS, also functions as a myelin-associated neurite outgrowth inhibitor (Hata et al, 2006;Yamashita et al, 2007). RGMa significantly inhibited neurite outgrowth in cultured neurons (Hata et al, 2006;Kubo et al, 2008). Furthermore, a neutralizing anti-RGMa antibody exhibits therapeutic effects on rat spinal cord injury by enhancing spinal axon outgrowth, suggesting that RGMa plays a key pathological role in suppressing axon regeneration and functional recovery after spinal cord injury (Hata et al, 2006;Yamashita et al, 2007).…”
Section: Spinal Cord Injurymentioning
confidence: 99%